PATHOLOGICAL CHANGES in LIVER, SPLEEN AND LYMPH NODES IN MICE TREATED WITH HYDATID CYST FLUID OF HUMAN ORIGIN AND ITS TOXIN FRACTIONS - Omaima Abbu (College of Education for Pure Sciences, 2019)
Swiss albino nice Mus musculus rvere injected, intraperitoneally, with hydatid cyst fluid (HCF) of human origin and its toxin fractions (TFs) at two concentrations (10 and 50 prglnir). obvious changes in the rveight and organ index of liver, spleen and lyrlph nodes of the injected tnice , in addition to histopathological changes , were observed. Results obtained indicate that there is a relationship between appearance of pathological lesions and changes in weight and organ index orur" above mentioned organs.